Openness and income disparities: does trade explain the 'Mezzogiorno' effect? - Claudia M. Buch; Paola Monti (Institut für Angewandte Wirtschaftsforschung (IAW), 2008)
Many theoretical models show that trade openness has positive welfare implications. Yet, openness might affect different social groups and regions asymmetrically, even within a given country. We use Italian regional data to answer the question whether trade openness affects within-country income differentials. In Italy, the more affluent regions are internationally more open than poorer ones not only with respect to trade in goods, but also with respect to FDI and international migration. Prima facie, there is a positive correlation between openness and per capita income. Studying this relationship empirically requires taking into account the endogenous component of openness. We apply panel cointegration and instrumental variables techniques to account for the endogeneity of trade. Our results show a positive link between trade openness and the level of income per capita.
Keywords: F2; F43; 330; Openness; growth; regional income disparities; Italian region